WAYS TO INCREASE THE ACTIVITIES OF THE MEDIA IN FORMING ECOLOGICAL CONSCIOUSNESS OF YOUTH IN UZBEKISTAN (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The article discusses the impact of the media on various aspects of modern society. Based on the analysis of the place and role of the mass media in the socio-political life of society, the formation of the worldview of the young generation, as well as the role in raising the level of environmental knowledge, proposals are formulated to activate the media in shaping the ecological consciousness of young people.